(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Synthetic antidepressants are used in the treatment of mental illness, however due to their side effects people are orienting towards the herbal product as an alternative therapy. The present study therefore, explores the role of C. lanatus (CL) seed extract in evaluating the fluoxetine-induced impaired sperm functions, and fertility of the depressed mice. Adult Swiss strain male mice were separated into six group. Every group contains six animals. Group I received vehicle-treated negative control while Groups II, III, IV, V and VI administered with reserpine (RES) at dose of 0.75 mg/kgBW/day, for 14 days to induce depression, fluoxetine (FLX) at the dose of 40 mg/kgBW/day in depressed mice (positive control) for 28 days, CL seed extract (300 mg/kgBW/day) only, in normal mice, and co-administrations of FLX (40 mg/kgBW/day) with low and high doses of seed extract of CL (150 mg/kgBW/day and 300 mg/kgBW/day) respectively, in the depressed mice for the same duration. Mice of Gr. II and Gr. IV did not alter the epididymal sperm parameters and fertility. However, significant alterations were observed in such parameters in the mice of Gr. III. Partial to complete restorations were noticed in such parameters in Gr. V and VI, as compared to the positive control of Gr. III. The findings suggest that CL seed extract may emerge as a potential herbal remedy to impaired fertility which could be of therapeutic drug in future.